Breast Feeding Practice Prevention for Nutritional Stunting of Children In Buginese Ethnicity - Agustian Ipa1,4 , Rudy Hartono 1,4, Sirajuddin 1, 2,4, Aswita Amir1,4, Sharifah Intan Zainun Sharif (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background. The practice of breastfeeding is very important to determine the quality of nutrient intake in children under two years. In ethnic Bugis. The purpose of this study was to determine the effect of breastfeeding on stunting prevention in ethnic Bugis. There is a cross-sectional study in this study. The sample size in this research is 300 mothers and children. The enumerators in this study were applied to undergraduate students of nutrition & dietetic programs in the Makassar Department of Nutrition Health Polytechnic, Indonesia. Research ethics was obtained at the Makassar Health Polytechnic Ethics Commission. Stunting risk factor data analysis with logistic regression test. The results showed that 32% of children were breastfed, with a frequency of 5-8 times / 24 hours breastfeeding. The reason for not breastfeeding a child is over 2 years old, the child refuses to breastfeed (10%), has 17.3% formula milk. Statistical analysis showed that breastfeeding (frequency of breastfeeding), p = 0.013, or 1.99 (1,148-3,173) was significant as stunting prevention. The conclusion is breastfeeding habits in ethnic Bugis can prevent stunting.